Reaction of Potato Varieties against Subterranean Pests - Lanunochetla; Alemla Ao, M.; Neog, Pankaj (International Journal of Bio-resource and Stress Management, 2023)
Ten potato varieties, viz. Kufri chandramukhi, Kufri jyoti, Kufri chipsona-I, Kufri chipsona-II, Kufri chipsona-III, Kufri anand, Kufri pukhraj, Kufri badshah, Kufri bahar and Kufri sindhuri were screened for their resistance/susceptibility against red ant, cutworm and wireworm at the Instructional-cum-Research Farm, School of Agricultural Sciences and Rural Development (SASRD), Nagaland University, Medziphema campus during 2005-07. The tuber damage by red ant ranged between 28.77 and 46.92% and yield loss ranged from 30.98 to 49.39%. The tuber damage by cutworm ranged from 8.42 to 18.87% and yield loss varied between 13.07 and 23.50%. Kufri sindhuri and Kufri badshah were the most resistant varieties against red ant and cutworm, while Kufri anand and Kufri chipsona-II were revealed as the most susceptible ones. Kufri chipsona-II recorded the lowest tuber damage by wireworm with 0.86% as well as with 3.85% yield loss, whereas the highest was recorded in Kufri pukhraj with 3.17% and 8.62%, respectively.